PROSES PENERIMAAN DIRI REMAJA TUNARUNGU BERPRESTASI - Evitasari, Ida Ayu Gede Sri; Widiasavitri, Putu Nugrahaeni; Herdiyanto, Yohanes Kartika (Jurnal Psikologi Udayana, 2015)
Deaf is a term that used to explained condition of individual who losing or disability to catch audio sensory through their hearing sense (Musyarrafah & Djalal, 2011). This condition contributes to some development aspect of human being, which is, social aspect and emotional aspect. Some of them successfully reconciled with themselves and accept their condition with a lot of great achievement. One of the others factor that drive deaf situation who shows an achievement is family assistance, however, uniquely there is a case in deaf who were not get physical assistance by their family and also can get great achievement. Aritama (2010) told that acceptance in any condition in self is the most basic thing if individual want to success and reconciled with state. Havighurst (in Sarwono, 2013) also adding that accept physical condition is one of the task in adolescence development. According that fact, this study would like to know self-acceptance in deaf adolescent who had achievement without physical assistance by their family.   This study using qualitative method and case study design. Collecting data in this study using interview, observation, and projective test to two deaf adolescence who had achievement without family assistance with different deaf history, that is, congenitally deaf and adventitiously deaf. To strengthened data study, this study used interview and observation to significant other of deaf adolescence.   Result in this study shows that deaf adolescent passing three phases in the process of self-acceptance, which proximal phase, conflict phase and accepting phase. The dynamics in every phase completely will be discussed based to the chronology of the life journey adolescence until they can accept their condition.   Keyword: self-acceptance process, deaf, achievement.